Pengaruh PBL Berorientasi One Stay Another Stray terhadap Keterampilan Komunikasi Siswa SMAN 1 Kapur IX: Penelitian - Amanda Yalsustri; Muhyiatul Fadilah; Rahmawati D; Helsa Rahmatika (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aimed to determine the effect of the Problem Based Learning (PBL) model oriented towards fun learning with the One Stay Another Stray (OSAS) technique on students' communication skills in the reproductive system material. This research was a pre-experimental study with a quantitative approach. The sample was class XI.F1 students of SMA Negeri 1 Kapur IX in the 2024/2025 academic year, selected through purposive sampling. Data were collected using essay tests on communication skills administered through pretest and posttest. The results showed that the average posttest score was higher than the pretest score, increasing from 38.79 to 84.39. Normality and homogeneity tests indicated that the data were normally distributed and homogeneous. The paired sample t-test revealed a significance value of 0.000 < 0.05, indicating a significant effect of the PBL model with OSAS on students’ communication skills. These findings suggest that implementing PBL combined with a fun learning approach and OSAS technique effectively enhances students’ communication abilities.